Trans-Tenon's retrobulbar triamcinolone infusion for the treatment of uveitis. Issue 8 (24th July 2003) - Okada, A A; Wakabayashi, T; Morimura, Y; Kawahara, S; Kojima, E; Asano, Y; Hida, T
Abstract : Aim: To assess efficacy and complications of trans-Tenon's retrobulbar infusion of triamcinolone acetonide for posterior uveitic inflammation. Methods: Non-randomised, uncontrolled, retrospective study of 51 eyes of 37 patients who underwent triamcinolone infusion for vitritis, cystoid macular oedema (CMO), or posterior retinal vasculitis using a long blunt cannula via an incision made through conjunctiva and Tenon's capsule. Results: Overall clinical efficacy was 86%; 96% for vitritis, 82% for CMO, and 33% for posterior retinal vasculitis. Mean visual acuity improved within 1 month after triamcinolone infusion (p <0.05). Cataract progression and intraocular pressure elevation were observed in 31% and 27% of eyes, respectively. Conclusion: Trans-Tenon's retrobulbar triamcinolone infusion may be a safe and effective treatment for posterior uveitic inflammation.